Discourse Analysis on A Governments’ COVID-19 Protocols Video Titled “Social Distancing” - Putra, Ngurah Rama Aditya (The Art of Teaching English as a Foreign Language (TATEFL), 2023)
The use of discourse amid the COVID-19 era to provide information about COVID-19 among the people was inseparable. The related information about COVID-19 was needed at that time to eliminate misunderstanding however, the discourse given through video tended to deliver hidden intentions. The focus of the present study was to attempt to find and elaborate on the hidden intentions of the use of a foreign language that was able in a video on President Joko Widodo’s YouTube channel titled “Social Distancing”. The research method used in the present study was a Three-dimensional model from Fairclough that consisted of three steps of analysis, namely description, interpretation, and explanation. Data was acquired from President Joko Widodo’s YouTube channel and other related references and collected by using an observation sheet instrument that employed four collection steps, namely watching/reviewing, marking, collecting, and displaying. The study concluded that there was a tendency to support the use of the English language in social practice to support globalization in Indonesia shown by the use of English words within the video. According to the study results people recommended increasing their awareness to avoid misunderstanding certain information.